Motivations, contradictions and ambiguities in the leadership of nurses in management positions in a university hospital - Clarice Maria Dall'Agnol; Gisela Maria Schebella Souto de Moura; Ana Maria Muller de Magalhaes; Maria Lucia Rodrigues Falk; Caren de Oliveira Riboldi; Andreia Peres de Oliveira (Universidade de São Paulo, 2013)
OBJECTIVE: to analyze the contradictions and ambiguities which permeate nurses' motivation for exercising leadership in management positions, in a university hospital. METHOD: this study has a qualitative approach and is exploratory and descriptive, and used a total of 33 semi-structured interviews which were submitted to thematic analysis. RESULTS: the information converged on five categories: Motivation to take on a management position; The view of nursing managers on the exercising of leadership; The emblematic aspect of working with people; Leadership in nursing - mediatory and conciliatory; Time: a dilemma between managing and caring. CONCLUSION: leading people can be both a great encouragement, and an impeding aspect, bearing in mind the nuances of teamwork and the complexity of the context in which this process is constructed. In addition to this, conciliatory and mediatory attitudes are shown to be fundamental for a healthy and productive organizational atmosphere; however, the lack of time was indicated as a dilemma between managing and caring.